Zawieranie i wykonywanie umów przez jednostki gospodarki uspołecznionej na przykładzie umowy dostawy - Guzewicz, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
Socialized economy units were special entities in the period of the Polish People’s Republic, and the regulations regarding them were in line with the authoritarian rule of that time. As civil law entities, socialized economy units have been subject to the provisions of the Civil Code since its entry into force in January 1965. However, in situations where it was required by “special trading needs”, the competent state administration bodies were entitled to regulate relations between socialized economy units in a different way. The interference of administrative bodies into civil law relations is connected with the implementation of the general objective of protecting the national interest. The aim of the article is to analyse the provisions regarding contractual relations between socialized economy units on the example of a supply agreement. It was one of two contracts in the new Civil Code (along with the construction works contract) to which only socialized economy units could be parties. The analysis in the specified historical period allowed for drawing conclusions regarding the mechanism of functioning of civil law institutions in the Polish People’s Republic in a situation where the parties to the contract were specific entities of the national economy.
Keywords: jednostki gospodarki uspołecznionej; prawo cywilne PRL; zobowiązanie umowne; zawieranie umów; wykonywanie umów; umowa dostawy